Da amministratore a manager - Rosini, Dario (Strumenti per la didattica e la ricerca, 2002)
The public sector is changing under the pressure of increased competition, reduced resources and citizens' awareness about their role as customers/users. There is therefore a need for new principles and new tools for public management. However, such managerial skills do not belong to the political sphere and these new tools cannot be imported from the private sector without undergoing a specific adaptation. Public managers therefore play a central role in this process of change: in fact, the aim to be pursued is essentially to have more results-oriented attitudes on their part, in order to make a better use of the available resources.